A Seasonal Analysis of Potential Wind Power for Armidale NSW, Australia - Maklad, Yasser; Glencross-Grant, Rex (International Journal of Energy Economics and Policy, 2014)
<!–[if gte mso 9]> <![endif]–> In this study, wind characteristics and wind energy potential of Armidale, which is a regional rural city (the highest in Australia) in the Northern Tablelands of New South Wales (NSW) are examined and analysed utilizing mean daily wind velocity observations collected during the period 1994 to 2010. The wind velocity distribution curves of Armidale are obtained by utilizing the Weibull statistical probability density function based on the observed wind velocity data. Seasonal and monthly mean wind power at 10, 30, 50, and 70 metres heights. It concluded that Armidale is an eligible city for utilizing wind power as it has sufficient potential wind resource available. As a means of demonstrating such potential, a technical assessment is made for estimating electricity generation utilizing realistic wind turbine models of capacity 2300 kW, 2400 kW and 2500 Kw. The annual estimated electricity generation output and capacity factor produced for three different wind turbines are calculated and found to be significantly promising from generation and financial perspectives. Keywords: Renewable energy; wind energy; Weibull distributions; Armidale city; regional rural Australia; electricity rates JEL Classifications: C1; C2; C3; C6; C9 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>